2022
DOI: 10.1111/cpr.13384
|View full text |Cite
|
Sign up to set email alerts
|

Selective utilization of non‐homologous end‐joining and homologous recombination for DNA repair during meiotic maturation in mouse oocytes

Abstract: DNA double-strand breaks (DSBs) are highly toxic lesions that can cause genomic instability and can be repaired by non-homologous end-joining (NHEJ) and homologous recombination (HR) pathways. Despite extensive studies about DSB repair pathways, the roles of each pathway during meiotic maturation in oocytes are not well understood. Here we show that oocytes selectively utilize NHEJ and HR to repair DSBs during meiotic maturation. Inhibition of NHEJ impaired the meiotic maturation of oocytes with DNA damage by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
(107 reference statements)
0
5
0
Order By: Relevance
“…The DSBs in oocytes are mainly repaired by two pathways, HR and NHEJ. Due to the presence of the sister chromatid in meiotic prophase oocytes, HR is considered to be the predominant repair pathway in arrested primordial follicles (131). Blocking apoptosis in primordial follicles can activate HR to remove DSBs efficiently (132), and key components of HR, such as RAD51 and BRCA2, are highly expressed in primordial follicle oocytes (133).…”
Section: Maintenance Of Genome Stability In Oocytesmentioning
confidence: 99%
“…The DSBs in oocytes are mainly repaired by two pathways, HR and NHEJ. Due to the presence of the sister chromatid in meiotic prophase oocytes, HR is considered to be the predominant repair pathway in arrested primordial follicles (131). Blocking apoptosis in primordial follicles can activate HR to remove DSBs efficiently (132), and key components of HR, such as RAD51 and BRCA2, are highly expressed in primordial follicle oocytes (133).…”
Section: Maintenance Of Genome Stability In Oocytesmentioning
confidence: 99%
“…However, it was also reported that “clean” DSBs with complementary overhangs can be accurately repaired by the classic NHEJ pathway, showing nearly equal efficiencies in the presence of a homologous template 84 , 89 . In oocytes, NHEJ was found to be the preferential repair pathway during MII, as the inhibition of NHEJ-related elements was associated with increased DNA damage signals and decreased developmental competence 78 , 79 . Moreover, oocytes exposed to etoposide at the prophase stage undergo an increase in SAC-mediated MI arrest upon NHEJ inhibition, along with partially impaired K-MT attachment 78 (Fig.…”
Section: Dna Repair During Meiotic Maturationmentioning
confidence: 99%
“…In oocytes, NHEJ was found to be the preferential repair pathway during MII, as the inhibition of NHEJ-related elements was associated with increased DNA damage signals and decreased developmental competence 78 , 79 . Moreover, oocytes exposed to etoposide at the prophase stage undergo an increase in SAC-mediated MI arrest upon NHEJ inhibition, along with partially impaired K-MT attachment 78 (Fig. 3 ).…”
Section: Dna Repair During Meiotic Maturationmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, BRCA2 is thought to be involved in mitosis following phosphorylation by CHK1/2 and PLK1. During the metaphase to anaphase transition, the attachment of duplicated chromosomes to the spindle relies on the spindle assembly checkpoint (SAC) [ 48 ]. This complex is composed, among other proteins, of budding uninhibited by benzimidazole-related 1 (BUBR1) protein which needs to be acetylated to interact with the anaphase promoting complex (APC/C).…”
Section: Brcamentioning
confidence: 99%